Evaluation of the Financial Literacy Among Academic Staff: An Exploratory Survey from University of Duhok - Shivan Mohammad (تنمیة الرافدین)
This study aims to evaluate the extent and level of financial literacy among academic staff of universities in the Kurdistan region of Iraq. A structured questionnaire was distributed via the official email of the quality assurance directorate, which reached more than 1500 academic staff; only 161 responded. revealing a significant lack of knowledge about managing personal finances, investment strategies, and financial markets. With 58% not holding foreign currency and only 8% correctly identifying essential financial statements, the findings highlight a pressing need for improved financial education. About 63% of respondents declared that they prefer to open and use government bank account instead of bank account because it’s less trusted and half of the respondents spent more than 150,000 Iraqi dinars for car fuel only per month. Besides half of the surveyed academic and administrative staff do not set aside funds. Recommendations include workshops, community support programs, and enhanced use of FinTech applications to empower individuals in managing their finances effectively and to foster better financial literacy among the population.